Asthma and risk of non-respiratory tract infection: a population-based case–control study. Issue 10 (3rd October 2013) - Bang, Duk Won; Yang, Hyeon J; Ryoo, Eell; Al-Hasan, Majdi N; Lahr, Brian; Baddour, Larry M; Yawn, Barbara P; Juhn, Young J
Abstract : Objectives: Asthmatics have increased risks of airway-related infections. Little is known about whether this is true for non-airway-related serious infections such as Escherichia coli bloodstream infection (BSI). We assessed whether asthma is associated with a risk of developing community-acquired E coli BSI. Design: The study was designed as a population-based retrospective case–control study. Setting: This population-based study was conducted in Olmsted County, Minnesota. Participants: The study included 259 all eligible community-acquired E coli BSI cases in Olmsted County, MN between 1998 and 2007 and 259 birthday-matched, gender-matched and residency-matched controls. Primary and secondary outcome measures: Only community-acquired E coli BSI cases as the primary outcome was included. Asthma status as an exposure was ascertained by predetermined criteria. An adjusted OR and 95% CI for the association between asthma and risk of community-acquired E coli BSI was calculated using conditional logistic regression. Results: Of 259 eligible cases, 179 (69%) were women and mean age was 61±22 years. Of the 259 cases 37 (14%) and 16 (6%) of 259 controls had a prior history of asthma (adjusted OR 2.74; 95% CI 1.11 to 6.76; p=0.029). The population attributable risk of asthma for community-acquired E coli BSI was 9%. Although not statistically significant, there was a borderline association between having a history of food allergy and increased risk of community-acquired E coli BSI (6% vs 2%; adjusted OR 3.51; 95% CI 0.94 to 13.11; p=0.062). Conclusions: Based on the findings of the current population-based, case–control investigation, a history of asthma may be associated with risk of community-acquired E coli BSI. The impact of asthma on risk of microbial infections may go beyond airways.